Cyberbullying: a critical perspective on cyberbullying victimization and the overlap between the roles of victims and aggressors - Ferreira, Fátima Abreu (2011)
The main objective of this research is to examine the national prevalence and scale of cyberbullying, how it takes place and the core characteristics (behaviors, frequency, and duration) of cyberbullying victimization. We also intend to analyze the existence of an overlap between the roles of victims and aggressors concerning this risk. In order to accomplish our goals we have made a cross cultural comparison between Portugal, Spain and the United Kingdom and developed a questionnaire (Online Victimization Assessment) that we have applied to a representative sample of students from ten to eighteen years old, from Portugal, Spain and the United Kingdom. Participants were students on randomly selected public and private schools and descriptive and inferential statistics were used to analyze data. Results reveal that cyberbullying is the most present risk in online youngsters’ exposure in the three contexts. We also identified the existence of an overlap between the roles of victims and aggressors, with older females, without parental supervision, revealing higher correlation levels. These results led us to conclude that the anonymity of the Internet and the fact of not having to deal directly with the consequences of their actions, can often led victims to engage in cyberbullying behaviors themselves.